Efeitos do tratamento com progesterona sobre a reatividade vascular coronariana dependente do endotélio em ratas ovariectomizadas - Cunha, Tagana Rosa da (2019)
Cardiovascular diseases are a leading cause of death in the world. Several studies have shown that the incidence of cardiovascular diseases in women in the fertile period is lower than in men of same the age group. This question seems to be related to the action of the female hormones that confer cardioprotection to the women. Classic hormone replacement therapy is made by estrogen and progesterone, and the beneficial effects of estrogen are well established. On the other hand, progesterone (P4) has different effect depending on the bed studied. For this reason, in the present study we investigated the effect of the progesterone treatment on endothelium dependent coronary vascular reactivity in female Wistar rats. For this study were selected adult rats with 8 weeks of life divided into SHAM, Ovariectomized (OVX), Ovariectomized and progesterone treated (OVX P4). The systolic blood pressure was measured by plethysmography. After euthanasia the hearts were removed and coronary vascular reactivity was assessed by modified Langendorff technique. Curve dose response of bradykinin (BK) was constructed followed by inhibitions with 100 μM L-NAME, 2.8 μM indomethacin (INDO), L-NAME + INDO or L-NAME + INDO + 0.75 μM clotrimazole (CLOT). Expression of the proteins, eNOS, Akt and gp91fox, was quantified by the Western blotting method. The dihydroethyde (DHE) protocol was used to quantify the superoxide anion concentration (O2●-), as well as the hydrogen peroxide (H2O2) production was evaluated by 2 ', 7'-dichlorofluorescein (DCF) protocol. Data were expressed as mean ± SEM and the comparison between groups was performed by 1 or 2-way ANOVA, followed by Tukey post hoc (p < 0.05). There was no statistical difference regarding systolic blood pressure. Baseline coronary perfusion pressure (CPP) was reduced by ovariectomy, although P4 treatment was able to prevent this reduction (SHAM = 88 ± 3, OVX = 70 ± 8, OVX P4 = 96 ± 8 mmHg). We observed that BK-induced endothelium-dependent coronary vasodilatation was impaired in the OVX group and maintained in the OVX P4 group. After isolated or conjugated inhibition of endothelium-dependent relaxation factors (NO, PGI2 and EDHF), we observed that BK-induced vasodilatation was greater in the OVX P4 group than in the other groups, and only the combined inhibition of the three relaxation factors abolished this response. Treatment with progesterone prevented oxidative stress induced by ovariectomy. These results suggest that progesterone has a beneficial action on the coronary vascular bed, preventing deleterious effects on the endothelium induced by the ovarian sex hormone deficiency promoted by ovariectomy.